Three Body Abrasive Wear Studies on Nanoclay/NanoTiO2 filled Basalt-Epoxy Composites. (2017) - Mahesha, C.R; Shivarudraiah,; Mohan, N; Suprabha, R.
Abstract: An investigation was made to evaluate the effect of the incorporation of nano titanium dioxide alone and in combination with nano clay on the abrasive wear behavior of basalt fabric– epoxy (BE) composites. A vacuum-assisted resin infusion (VARI) technique was employed to obtain a series of BE composites. The effect of different loads (22 and 32 N) and abrading distances from 280 to 1120 m on the performance of the wear resistance of the composites were measured.The wear volume loss increases with increasing load/abrading distance. However, the specific wear rate decreases with increase in abrading distance and increases with the load. It was revealed that the better wear resistance of the Clay-TiO2 basalt epoxy hybrid composite was due to a synergistic effect between the nano Clay-TiO2 . The worn surfaces were examined using scanning electron microscopy (SEM).